Increased leptin/leptin receptor pathway affects systemic and airway inflammation in COPD former smokers - Bruno A (Dove Medical Press, 2011)
Andreina Bruno1, Marinella Alessi2, Simona Soresi2, Anna Bonanno1, Loredana Riccobono1, Angela Marina Montalbano1, Giusy Daniela Albano1, Mark Gjomarkaj1, Mirella Profita11Institute of Biomedicine and Molecular Immunology, Italian National Research Council, Palermo, Italy; 2Dipartimento Biomedico di Biomedicina Interna e Specialistica, University Palermo, ItalyBackground: Leptin, a hormone produced mainly by adipose tissue, regulates food intake and energy expenditure. It is involved in inflammatory diseases such as chronic obstructive pulmonary disease (COPD) and its deficiency is associated with increased susceptibility to the infection. The leptin receptor is expressed in the lung and in the neutrophils.Methods: We measured the levels of leptin, tumor necrosis factor alpha (TNF-a) and soluble form of intercellular adhesion molecule-1 (sICAM-1) in sputum and plasma from 27 smoker and former smoker patients with stable COPD using ELISA methods. Further we analyzed leptin and its receptor expression in sputum cells from 16 COPD patients using immunocytochemistry.Results: In plasma of COPD patients, leptin was inversely correlated with TNF-a and positively correlated with the patient weight, whereas the levels of sICAM-1 were positively correlated with TNF-a. In sputum of COPD patients leptin levels were correlated with forced expiratory volume in 1 second/forced vitality capacity. Additionally, increased levels of sputum leptin and TNF-a were observed in COPD former smokers rather than smokers. Further the expression of leptin receptor in sputum neutrophils was significantly higher in COPD former smokers than in smokers, and the expression of leptin and its receptor was positively correlated in neutrophils of COPD former smokers.Conclusion: Our findings suggest a role of leptin in the local and systemic inflammation of COPD and, taking into account the involvement of neutrophils in this inflammatory disease, describe a novel aspect of the leptin/leptin receptor pathway in the regulation of host defense after smoking cessation.Keywords: COPD, smokers, inflammation, leptin, neutrophils